2016
DOI: 10.1021/acs.biochem.6b00263
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Reactions of the LOV and LOV-Linker Domains of the Blue Light Sensor Protein YtvA

Abstract: YtvA is a blue light sensor protein composed of an N-terminal LOV (light-oxygen-voltage) domain, a linker helix, and the C-terminal sulfate transporter and anti-σ factor antagonist domain. YtvA is believed to act as a positive regulator for light and salt stress responses by regulating the σB transcription factor. Although its biological function has been studied, the reaction dynamics and molecular mechanism underlying the function are not well understood. To improve our understanding of the signaling mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 36 publications
6
28
0
Order By: Relevance
“…Evidently, the A 0 a helices are required for signal amplification. This sentiment is in line with the recent finding that BsYtvA-LOV undergoes light-induced expansion while BsYtvA-LOV lacking the A 0 a helices does not (Choi et al, 2016). It also underpins the importance of the A 0 a helix for signal transduction, as exemplified by the inverse signaling logic of certain YF1 variants, which carry mutations in this region (Gleichmann et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Evidently, the A 0 a helices are required for signal amplification. This sentiment is in line with the recent finding that BsYtvA-LOV undergoes light-induced expansion while BsYtvA-LOV lacking the A 0 a helices does not (Choi et al, 2016). It also underpins the importance of the A 0 a helix for signal transduction, as exemplified by the inverse signaling logic of certain YF1 variants, which carry mutations in this region (Gleichmann et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Intriguingly, a parallel investigation by X-ray solution scattering demonstrates essentially the same light-induced transitions within the isolated LOV photosensor dimer 32 . Moreover, transient grating studies on the isolated Bs YtvA LOV photosensor recently revealed an increase in the hydrodynamic radius upon blue-light absorption 33 which is fully consistent with the light-induced pivot transition observed presently by EPR spectroscopy. We thus deem it likely that this structural mode also underpins photoreception in full-length Bs YtvA.
Figure 4Schematic of the transition from dark-adapted to light-adapted state of YF1 and proposed signal transduction mechanism.
…”
Section: Discussionsupporting
confidence: 84%
“…The LOV domain without J α ‐linker (but with the N‐cap) appears to be homodimeric in the dark, but mainly monomeric after light activation; the presence of the J α ‐linker ensured stable dimerization under both light and dark conditions, as previously reported for the full‐length protein . Instead, thermal grating measurements showed no light‐induced conformational changes for the LOV core, at least on the ms timescale, but comparable changes (within 70 μs) when the N‐cap alone or N‐cap + J α ‐linker is present . Choi et al ., nevertheless, could not detect any change in extent of oligomerization by means of size exclusion chromatography (SEC), in partial discrepancy with the native gel analysis .…”
Section: Exploiting Modularity In Signal Transmissionsupporting
confidence: 65%
“…As shown by structural data on a chimeric protein, bearing the Bs YtvA–LOV domain fused to a heterologous HisK , signal transmission is thought to proceed via a torque mechanism of the coiled J α ‐linker . Data obtained from thermal grating, a photocalorimetric technique, have yielded the kinetics of these two signal transmission mechanisms: <70 μs for the postulated “torque” in Bs YtvA J α ‐linker (plus a further conformational change with a time constant of 530 μs), compared to 300 μs for the J α ‐linker detachment in As phot‐LOV2, followed by unfolding with a time constant of one ms . If this same dynamics difference held at physiological temperature in host cells, the “torque” mechanism would thus be kinetically advantageous for optogenetic applications.…”
Section: Exploiting Modularity In Signal Transmissionmentioning
confidence: 99%